The Grid Makati DRRM Complex - Villanueva, Cristouffer Gabriel R.; Tomeldan, Michael V. (Quezon City College of Architecture, University of the Philippines Diliman, 2020)
Over 30 major earthquakes and thousands of typhoons have passed through our country in the last 2 decades. This is almost the same amount of time that the PD 1566, the first dedicated disaster risk reduction management law in our country, was passed. Yet there are still a lot of communities who can't cope properly whenever nature strikes. Even 2019's richest city of the Philippines -- Makati, still face this problem in their Disaster Risk Reduction Management. Even more so because as proven throughout time, they have been making great strides in both sides of the problem, internally and externally. Internally they train their volunteers on a regular basis and externally they use the different barangay officials to make sure all the citizens of Makati are informed on what to do. Even with this, the situation has not significantly changed. In every typhoon most barangays still experience heavy flooding and have had to evacuate from their house or office every time. This project is done by using the both ideas from the community and plans from the DRRM officials to create an efficient and effective learning facility for disaster mitigation. The facility's methods of learning is divided into formal and informal. Formal learnings is geared towards to responders and volunteers who want to learn the proper protocols and maybe build a career as a DRRM responder. While informal learning is for everyone else, this will be done through a visual and experiential museum showcasing the different natural threats in the country and how to deal with it. This is done for the citizens to be more equipped in times of disasters which should ultimately lower the level of vulnerability of the city then the country.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Disaster relief facilities; Emergency management